Identification, characterisation of microplastic and their effects on aquatic organisms. Issue 10 (26th November 2022) - Alak, Gonca; Uçar, Arzu; Parlak, Veysel; Atamanalp, Muhammed
ABSTRACT: Due to global warming, drought, population growth and industrialisation, existing water resources are rapidly being depleted and polluted. Pollution caused by millions of plastic waste reaching water resources seriously threatens the aquatic environment. This manuscript reviews the current state of knowledge about microplastics in the aquatic ecosystem, their analysis and detection methods, and their effects on aquatic organisms. In addition to the measurement methods, alternative new methods and the relevant findings for MPs, including abundance, size, shapes, colours and polymer types are summarised considering the literature. In addition, the effects of microplastics on the aquatic ecosystem especially fish had been evaluated. In the light of the completed researches, it is understood that abundance and size of MP s are connected with fish species, tissue type and feeding regime. KOH for the digestion in tissues and fenton reagent for sediment samples were found as more suitable techniques. FTIR and Raman spectroscopy were more advantaged because they are not only fast – easy but also have repeatable specifications.